The Influence of the Heat Transfer Mode on the Stability of Foam Extinguishing Agents - Xia Zhou; Zhihao An; Ziheng Liu; Hongjie Ha; Yixuan Li; Renming Pan (Fire, 2024)
The mass loss mechanisms of an aqueous film-forming foam (AF foam), an AR/AFFF water-soluble film-forming foam extinguishing agent (AR foam), and a Class A foam extinguishing agent (A foam) at different levels of thermal radiation, thermal convection, and heat conduction intensity were studied. At a relatively low thermal radiation intensity, the liquid separation rate of the AF, AR, and A foams is related to the properties of the foam itself, such as viscosity and surface/interface tension, which are relatively independent of the external radiation heat flux of the foam. At low radiation intensity (15 kW/m2 and 25 kW/m2), the liquid separation rate of the AF and A foams is relatively stable. When the heat flux intensity is 35 kW/m2, the liquid separation rate of the AF and A foams increases notably, which may be mainly due to the rapid decrease in foam viscosity. And the mass loss behavior is dominated by liquid separation in the AF, AR, and A foams under the influence of thermal radiation and thermal convection. Under the same experimental conditions, the liquid separation rate of AF is the fastest. There is no significant difference in the evaporation rates of the three kinds of foam in the same heat conduction condition. In addition, the AR and A foams usually have a 25% longer liquid separation time (t) under thermal radiation and thermal convection, and the thermal stability is better than AF foam. The temperature reached by the AF foam layer under thermal convection was lower than that of the AR and A foams, and the time for the foam layer to reach the highest temperature under heat conduction was longer than that of the AR and A foams.